(untitled) - Ferrell, O. C. (New York, 2011)
BUSINESS was created with students' and professors' needs in mind. Students receive a cost-effective, easy to read text complete with study resources (both print and online) to help them review for tests and apply chapter concepts. Professors receive a text that contains all the pertinent information we know they cover in Introduction to Business - yet in a more condensed format that is easier for students and instructors to cover in 1 term. It also contains gradable online assignments for instructors to assign. M: BUSINESS also includes comprehensive teaching support and online supplements
Keywords: Business,Kinh doanh